Indonesian EFL university students’ ChatGPT acceptance: a cross-sectional study - Aji Budi Rinekso; Rojab Siti Rodliyah; Pupung Purnawarman; Nenden Sri Lengkanawati (Journal of Education and Learning (EduLearn), 2026)
Informed by the technology acceptance model (TAM), this cross-sectional study investigated to what extent ChatGPT is perceived by English as a foreign language (EFL) university students. A total of 149 Indonesian EFL university students took part in filling out a questionnaire representing the five variables of TAM including perceived ease of use (PEU), perceived usefulness (PU), attitude toward using (ATU), behavioral intention to use (BIU), and actual use (AU). The data were analyzed based on partial least square structural equation modelling (PLS-SEM) using SmartPLS v.4. The results showed that all of TAM variables contributed to explaining the participants’ use of ChatGPT, except the path ATU─BIU (p=0.229), which was not significant due to the overshadowing influence of perceived usefulness. This indicated that the participants were mainly motivated by the practical benefits of ChatGPT in enhancing language learning. Therefore, this study suggests that educators and curriculum designers might consider integrating ChatGPT’s utility into language learning tasks to foster students’ effective yet critical engagement with the tool. Pedagogically, this study provides empirical evidence on the potential of ChatGPT to be adopted in future university-level language education, while acknowledging the need for further research on its limitations.